Impact of vaccine platform and BCG vaccination on antibody responses to COVID-19 vaccination - Messina, Nicole L.; Sperotto, Mariana G.; Puga, Marco A. M.; da Silva, Patricia V.; de Oliveira, Roberto D.; Moore, Cecilia L.; Pittet, Laure F.; Jamieson, Tenaya; Dalcolmo, Margareth; dos Santos, Glauce; Jardim, Bruno; Lacerda, Marcus V. G.; et al. (Frontiers in Immunology, 2023)
Multiple factors, including vaccine platform and prior vaccinations, influence vaccine responses. We compared antibody responses to CoronaVac (Sinovac) and ChAdOx1-S (AstraZeneca-Oxford) vaccination in 874 healthcare workers in Brazil. As participants were randomised to BCG vaccination or placebo in the preceding 0-6 months as part of the BCG vaccination to reduce the impact of COVID-19 in healthcare workers (BRACE) trial, we also investigated the influence of recent BCG vaccination on antibody responses to these COVID-19 vaccines. Twenty-eight days after the second dose of each vaccine, ChAdOx1-S induced a stronger anti-spike IgG response than CoronaVac vaccination. Recent BCG vaccination did not impact IgG antibody responses to ChAdOx1-S or CoronaVac.